The National Counterterrorism Agency's Efforts to Improve Intelligence Institution Collaboration in Countering Terrorism in Indonesia - Hidayat, Cecep; Zarkasyi, Fajar Imam (International Journal of Social Science and Religion (IJSSR), 2024)
Lack of intelligence collaboration is considered to be one of the fundamental problems in tackling terrorism in Indonesia. However, amidst the negative attention, there are efforts by BNPT (National Counterterrorism Agency) to improve collaboration between intelligence agencies. By using Weiss's theory to analyze various statements from public officials and state institutions regarding the issue of intelligence agency cooperation in Indonesia, this paper finds two important conclusions. First, efforts to encourage the formation of intelligence collaboration have actually been carried out by BNPT by equalizing perceptions among various intelligence agencies in viewing the problems and issues of terrorism. This is evidenced by a series of training conducted by BNPT in the period 2020-2023 which aims to encourage synergy between intelligence agencies related to terrorism issues. Second, still in line with what Weiss revealed, BNPT's steps with this series of training are inseparable from the external pressure sourced from public opinion in encouraging the formation of cooperation. In this case, the strong public demand for the importance of intelligence collaboration in dealing with the problem of terrorism is inseparable from the intensity of terrorism attacks that occurred from 2016 to 2021. The bomb attacks that occurred during this period led to polemics over the function of intelligence, which in turn shows the importance of intelligence collaboration as an important component of counterterrorism.